Analisis Beban Kerja Pegawai pada Kantor Kecamatan Gubeng Kota Surabaya - Warda Akhadatus Zuhro; Lukman Arif (VISA: Journal of Vision and Ideas, 2024)
The function of the sub-district in the local government system is at a crucial level, considering its position which directly relates to and provides direct public services to the local community. Public services themselves have great demands from the public, the public sector is asked to provide excellent service by showing high professionalism. However, according to the Central Statistics Agency, in 2024, the number of Civil Servants (PNS) in Indonesia will decrease from 2015-2023. This causes employee workload to increase, due to bureaucratic reform which is still in progress. In Gubeng District, it was found that there were still not enough employees to be able to meet the existing workload. This study aims to conduct a workload analysis in the Gubeng District Work Unit by referring to PermenPANRB No. 1 of 2020 concerning Guidelines for Job Analysis and Workload Analysis. This research uses a qualitative descriptive method, where this research focuses on an organizational approach, a job analysis approach, and an administrative approach by conducting direct interviews with all Gubeng District staff and collecting data via the e-ABK website. Based on the research results, it was found that the job analysis of employees at the Gubeng sub-district office was considered to be overloaded, so it was necessary to add additional employees so that all tasks were carried out well and did not overlap.